OPTIMALISASI PERAN E-GOVERNMENT DALAM MENINGKATKAN KUALITAS PELAYANAN PUBLIK - Silvia Dwi Amanda Wijaya; Herbasuki Nurcahyanto; Aufarul Marom (Journal of Public Policy and Management Review, 2023)
The application of E-Government through the sipenduduk.pekanbaru.go.id website is based on providing easy access to services for the community in managing administrative and population documents. The problem of this study is the network (server down) and there are still many people who do not know the mechanism for using sipenduduk.pekanbaru.go.id website. The purpose of the study is to analyze the optimization process and the obstacles that occur in the application of the sipenduduk.pekanbaru.go.id website. Efforts to answer problems and research objectives use the theory of successful elements of E-Government development using descriptive research methods and qualitative approaches. The data obtained in this study through observation, documentation, and interviews.The results of this study show that the Optimization of the Role of E-Government in Improving the Quality of Public Services (Study on Website sipenduduk.pekanbaru.go.id) conducted by the Pekanbaru City Population and Civil Registration Service has made optimization efforts on the sipenduduk.pekanbaru.go.id website well. This is seen from 3 indicators, namely: Support, Capacity, and Value. Optimization efforts in the use of this website have not been fully efficient due to several obstacles that occur, namely, limited infrastructure and culture that come from the lack of literacy and enthusiasm of the community. It is recommended that the Pekanbaru City Population and Civil Registration Service can prepare a private server or use a 3rd party server so that there are no limited server quotas, conduct socialization involving the lowest level officials, and it is hoped that there will be full participation and literacy from the community in utilizing the website.